FUNDAMENTAL PRINCIPLES OF MINERAL AND COAL RESOURCES MANAGEMENT IN THE REGIONAL AUTONOMY ERA - Azmi Fendri; Busyra Azheri (Kanun Jurnal Ilmu Hukum, 2022)
The management of mineral and coal resources is affected by the shift in the paradigm of regional government administration, which now emphasizes aspects of regional autonomy. Law Number 23, 2014 concerning Regional Government, which genuinely adheres to the maxim of maximal regional autonomy, appears to be incompatible with Law Number 3, 2020 concerning the revision of Law Number 4, 2009 on Mineral and Coal Mining. In practice, this results in a variety of interpretations of the nature and significance of regional autonomy, which ultimately has repercussions for the management of mineral and coal resources. This research aims to investigate the significance and nature of regional autonomy in connection to the management of mineral and coal resources. This is doctrinal legal research and a philosophical approach is applied based on legal principles. The findings are the fundamental principles of managing mineral and coal resources in the future era of regional autonomy focuses on returning to the principle of being a state, which means that the use of mineral and coal resources must be in accordance with the ideals of the state outlined in paragraph 4 of the Preamble of the 1945 Constitution, aspects of environmental harmonization and spatial alignment and the application of the principle of proportionality in regulating government and local government authorities.